Implementation of the MathCityMap Application to Increase Students' Mathematical Problem-Solving Skills: A Systematic Literature Review - Paramitha, Witha; Agoestanto, Arief (Jurnal Pendidikan Matematika, 2023)
The growing research on the use of the MathCityMap application in mathematics education necessitates a summary of its finding. MathCityMap is an application supported by the use of mobile technology to provide real visualization of mathematics concepts to students in order to improve students' mathematical problem-solving skills. This study aims to provide an overview of the application of the MathCityMap application to increase students' mathematical problem-solving skills. A systematic literature review (SLR) was used to synthesize research relevant to the objectives of this study. Research steps using Systematic Literature Review are formulating research questions, applying inclusion criteria, looking for studies related to the topic, selecting some studies to be the main study, analyzing data from the studies’ results, and compiling them into research reports. Through Publish or Perish, Google Scholar, Directory of Open Access Journals (DOAJ), and Education Resources Information Centre (ERIC) it was obtained that 16 primary studies were published from 2013 to 2023 that fitted the inclusion criteria for further analysis. The results of this study conclude that the MathCityMap application is effective in improving students' mathematical problem-solving skills. The integration of the MathCityMap application with learning models can be used by teachers to help students complete various project-based assignments and improve mathematics problems. The results of this study help teachers and researchers to understand how the MathCityMap application can be applied in learning mathematics to improve students' mathematical problem-solving skills. Penelitian tentang implementasi aplikasi MathCityMap dalam pembelajaran matematika semakin banyak dilakukan, sehingga perlu adanya penelitian yang merangkum hasil temuan penelitian aplikasi MathCityMap dalam pembelajaran Matematika. MathCityMap adalah aplikasi yang didukung dengan pemanfaatan teknologi mobile untuk memberikan visualisasi konsep matematika secara nyata kepada siswa guna meningkatkan kemampuan pemecahan masalah matematis siswa. Penelitian ini bertujuan untuk memberikan gambaran penerapan aplikasi MathCityMap terhadap kemampuan pemecahan masalah matematis siswa. Metode penelitian yang digunakan adalah Systematic Literature Review (SLR). Langkah-langkah penelitian dengan menggunakan Systematic Literature Review adalah merumuskan pertanyaan penelitian, menerapkan kriteria inklusi, mencari kajian yang berkaitan dengan topik, memilih beberapa kajian untuk menjadi kajian utama, menganalisis data dari hasil kajian, dan menyusunnya menjadi laporan penelitian. Sintesis studi yang relevan dengan tujuan penelitian ini dilakukan menggunakan Publish or Perish, Google Scholar, Directory of Open Access Journals (DOAJ), dan Education Resources Information Centre (ERIC) dimana diperoleh 16 studi primer yang diterbitkan dari tahun 2013 hingga tahun 2023. Hasil penelitian memberikan informasi bahwa aplikasi MathCityMap efektif untuk meningkatkan kemampuan pemecahan masalah matematis siswa. Integrasi MathCityMap dengan model pembelajaran dapat digunakan guru untuk membantu siswa menyelesaikan berbagai tugas berbasis proyek dan memecahkan masalah. Hasil penelitian ini membantu guru dan peneliti untuk memahami bagaimana aplikasi MathCityMap dapat diterapkan dalam pembelajaran matematika untuk meningkatkan kemampuan pemecahan masalah matematis siswa.